Temozolomide treatment can improve overall survival in aggressive pituitary tumors and pituitary carcinomas. Issue 6 (June 2017) - Lasolle, Hélène; Cortet, Christine; Castinetti, Fréderic; Cloix, Lucie; Caron, Philippe; Delemer, Brigitte; Desailloud, Rachel; Jublanc, Christel; Lebrun-Frenay, Christine; Sadoul, Jean-Louis; Taillandier, Luc; Batisse-Lignier, Marie; et al.
Abstract : Objectives: Only few retrospective studies have reported an efficacy rate of temozolomide (TMZ) in pituitary tumors (PT), all around 50%. However, the long-term survival of treated patients is rarely evaluated. We therefore aimed to describe the use of TMZ on PT in clinical practice and evaluate the long-term survival. Design: Multicenter retrospective study by members of the French Society of Endocrinology. Methods: Forty-three patients (14 women) treated with TMZ between 2006 and 2016 were included. Most tumors were corticotroph ( n = 23) or lactotroph ( n = 13), and 14 were carcinomas. Clinical/pathological characteristics of PT, as well as data from treatment evaluation and from the last follow-up were recorded. A partial response was considered as a decrease in the maximal tumor diameter by more than 30% and/or in the hormonal rate by more than 50% at the end of treatment. Results: The median treatment duration was 6.5 cycles (range 2–24), using a standard regimen for most and combined radiotherapy for six. Twenty-two patients (51.2%) were considered as responders. Silent tumor at diagnosis was associated with a poor response. The median follow-up after the end of treatment was 16 months (0–72). Overall survival was significantly higher among responders ( P = 0.002); however, ten patients relapsed 5 months (0–57) after the end of TMZ treatment, five in whom TMZ was reinitiated without success. Discussion: Patients in our series showed a 51.2% response rate to TMZ, with an improved survival among responders despite frequent relapses. Our study highlights the high variability and lack of standardization of treatment protocols.